2011
DOI: 10.1039/c1em10213c
|View full text |Cite
|
Sign up to set email alerts
|

Sources and fate of Salmonella and fecal indicator bacteria in an urban creek

Abstract: This research aimed to understand the sources and fate of Salmonella and fecal bacteria in urban surface waters. An urban creek (San Pedro Creek, California, USA) that had unusually high levels of Salmonella and fecal bacteria relative to other nearby waterbodies was chosen as a model field site. State of the art microbiological methods were used in concert with modeling to investigate Salmonella and fecal bacteria sources, and determine field-relevant dark inactivation and photoinactivation rates. Three along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…Bradshaw et al (2016) also reported that the odds of stx detection increased by a factor of 2 for each log 10 increase in ruminant FST marker concentration, which is similar to the odds ratio calculated here (OR = 1.6; 95% CI = 1.1, 2.4). The identification of an association between hostassociated FST markers, and Salmonella and eaeA-stx codetection is also consistent with the associations between spatial factors and microbial target detection identified here and in past studies (Sassoubre et al, 2011;Walters et al, 2011;Wilkes et al, 2011;Bradshaw et al, 2016). For instance, Wilkes et al (2011) identified a positive association between pasture being present 0-5 km upstream of a sampling site, and an increased likelihood of isolating E. coli O157:H7 from water samples collected in Ontario, Canada.…”
Section: Salmonella Isolation and Eaea-stx Codetection Were Associatesupporting
confidence: 87%
“…Bradshaw et al (2016) also reported that the odds of stx detection increased by a factor of 2 for each log 10 increase in ruminant FST marker concentration, which is similar to the odds ratio calculated here (OR = 1.6; 95% CI = 1.1, 2.4). The identification of an association between hostassociated FST markers, and Salmonella and eaeA-stx codetection is also consistent with the associations between spatial factors and microbial target detection identified here and in past studies (Sassoubre et al, 2011;Walters et al, 2011;Wilkes et al, 2011;Bradshaw et al, 2016). For instance, Wilkes et al (2011) identified a positive association between pasture being present 0-5 km upstream of a sampling site, and an increased likelihood of isolating E. coli O157:H7 from water samples collected in Ontario, Canada.…”
Section: Salmonella Isolation and Eaea-stx Codetection Were Associatesupporting
confidence: 87%
“…The concentrations of these bacteria, however, are known to be highly variable (6,7,59,60). Intensive field studies show that their concentrations fluctuate on diurnal timescales due to sunlight exposure; concentrations drop during sunlit hours and rise after the sun sets (8,21,50,60,61). While enterococcal photoinactivation is well documented, the mechanisms of inactivation are not well understood, limiting our ability to predict when the process will be important under the wide range of conditions that exist in natural and engineered systems.…”
mentioning
confidence: 99%
“…bacterial inactivation in natural waters. The inactivation of Escherichia coli and to a lesser extent enterococci has been measured in a wide range of sunlit waters and the observed inactivation rate constants vary over several orders of magnitude 15,[21][22][23][24][25][26] . There are limited studies on sunlight inactivation of waterborne bacterial pathogens such as Campylobacter, Vibrio cholerae, Shigella,…”
Section: It Is Presently Unknown To What Extent the Three Different Mmentioning
confidence: 99%